Low-Cost Activated Carbon Electrodes from Waste Maple Leaves for Organic Electric Double-Layer Capacitors. Issue 8 (20th August 2021) - Jung, Meenkyoung; Yang, Inchan; Yoo, Jihoon; Kim, Myung-Soo; Jung, Ji Chul
Abstract : We successfully prepared activated carbons (AC) derived from waste maple leaves and applied them to electrode materials for organic electric double-layer capacitors (EDLC). Maple leaves were efficiently converted into ACs based on their eco-friendliness, cost effectiveness, oxygen-containing, and inorganic components that can promote forming pores. Accordingly, waste maple leaves were carbonized under flowing nitrogen, and subsequently activated using CO2 or KOH to be converted into ACs with large specific surface areas. Particularly, a maple carbon sample chemically activated at 800 °C with KOH (MCK800) showed not only a large specific surface area but also well-developed pore structure, and the properties of MCK800 were superior to those of a commercially available activated carbon (YP50f). These remarkable properties of MCK800 led to considerable capacitance properties and high electrical conductivity in an organic EDLC system. Finally, we concluded that waste maple leaves are potential candidates for low-cost starting materials of organic EDLC electrodes.